Studi Kasus: Psikoedukasi Keluarga Online Untuk Menurunkan Beban Perawatan Pada Keluarga Pasien Skizofrenia - Andalasari, Niken; Keliat, Budi Anna; Susanti, Herni (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: The role of the family is very important in the care of schizophrenic patients, but it can carry out the burden of care that will directly affect the progress of care for schizophrenic patients to reduce the burden on families in caring for schizophrenic patients. Methods: This article using case study research design. Data was collected by online interview dan observation using video call, The instrument Burden Assessment Schedule (BAS) questionnaire was used to measure the family. The online intervention family psychoeducation was applied to this study. Results: The nurse performs individual scanning, followed by assessing the family burden using the BAS questionnaire before and after performing family psychoeducation for 6 sessions. The entire nursing care process is carried out online using video calls for 2 times per week with a total of 6 meetings for 3 weeks. The result is showing after the intervention there is a decrease in the BAS score from 32 to 25.Conclusion: After performed in 3 weeks family psychoeducation can reduce the burden of care experienced by families so that families can identify problems faced, manage stress, and share roles in caring for patients.